2018
DOI: 10.1021/acsnano.8b02793
|View full text |Cite
|
Sign up to set email alerts
|

High-Quality In-Plane Aligned CsPbX3 Perovskite Nanowire Lasers with Composition-Dependent Strong Exciton–Photon Coupling

Abstract: Cesium lead halide perovskite nanowires have emerged as promising low-dimensional semiconductor structures for integrated photonic applications. Understanding light-matter interactions in a nanowire cavity is of both fundamental and practical interest in designing low-power-consumption nanoscale light sources. In this work, high-quality in-plane aligned halide perovskite CsPbX (X = Cl, Br, I) nanowires are synthesized by a vapor growth method on an annealed M-plane sapphire substrate. Large-area nanowire laser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
225
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(229 citation statements)
references
References 46 publications
4
225
0
Order By: Relevance
“…CsPbX 3 nanocrystals have been incorporated into solar cells achieving a record 13.4 % power conversion efficiency (PCE). [6][7][8][9][10] In addition to light absorption or conversion for energy capture, these materials have been reported for possible use in laser media, [11][12][13][14] LEDs, [15][16][17][18] and photodetectors. [12,[19][20] Most reported syntheses of CsPbX 3 follow the work of Protesescu et al who demonstrated a simple, solution-based synthesis for nanocrystals with high luminescence.…”
Section: Introductionmentioning
confidence: 99%
“…CsPbX 3 nanocrystals have been incorporated into solar cells achieving a record 13.4 % power conversion efficiency (PCE). [6][7][8][9][10] In addition to light absorption or conversion for energy capture, these materials have been reported for possible use in laser media, [11][12][13][14] LEDs, [15][16][17][18] and photodetectors. [12,[19][20] Most reported syntheses of CsPbX 3 follow the work of Protesescu et al who demonstrated a simple, solution-based synthesis for nanocrystals with high luminescence.…”
Section: Introductionmentioning
confidence: 99%
“…This new perovskite can serve as ag ain medium and microcavity to achieve broadband (475-540 nm) single-mode lasing with ahigh Qofabout 2100.All-inorganic metal halide perovskites of the form CsPbX 3 (X = Cl, Br,I ), owing to their remarkable properties,a re attracting increasing attention for use in optoelectronic devices such as solar cells,l ight-emitting diodes (LEDs), and semiconductor nanolasers. [1][2][3][4][5][6][7][8][9][10] Such all-inorganic perovskites exhibit superior properties,including improved photo-…”
mentioning
confidence: 99%
“…Anisotropic nanowires can serve as a waveguide along the axial direction, and the two end facets can form a Fabry‐Perot cavity for optical amplification . Therefore, the single‐crystalline perovskite nanowires with ideal facets are good candidates for the optically pumped lasers.…”
Section: D Metal Halide Perovskitesmentioning
confidence: 99%
“…Anisotropic nanowires can serve as a waveguide along the axial direction, and the two end facets can form a Fabry-Perot cavity for optical amplification. 187,206 Therefore, the single-crystalline perovskite nanowires with ideal facets are good candidates for the optically pumped lasers. The first lead halide perovskite nanowire-based laser was demonstrated by Zhu et al (Figure 12A) from a room-temperature solution method, showing wavelength-tunable lasing with very low thresholds (220 nJ cm −2 ) and a high-quality factor (Q~3600) ( Figure 12B).…”
Section: Lasersmentioning
confidence: 99%